Antioxidant Activity of Non-Volatile Lime (Citrus aurantifolia Swingle) Extract - Permadi, Nandang; Julaeha, Euis; Rosandi, Yudi; Nurzaman, Mohamad (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2021)
The paper reports the antioxidant activity of a non-volatile fraction of lime processing byproducts from the lime syrup home industry. The activity was measured by spectrophotometry to obtain the 50% inhibition concentration (IC50) using the 2,2- diphenyl-1-picrylhydrazyl (DPPH) method. The sample was extracted by the maceration method with n-hexane, ethyl-acetate, and ethyl-ethanol. The IC50 values of 681 ppm, 458 ppm, and 2,775 ppm were n-hexane, ethyl-acetate, and ethyl-ethanol. The experiments concluded that the ethyl-acetate extract provides the best inhibition value to scavenge free-radicals DPPH. The HPLC and mass spectroscopy were measured to find out the content and group of active compounds. The significant compounds consisted of naringin, poncirin, or neoponcirin, which are known as antioxidant substances. The result shows the potential application of the lime by-products, its volatile fraction, and the nonvolatile fraction, which is the production residue of lime peel. This work can be applied as an alternative to zero-waste lime production, which may benefit the industry and the environment.